WebGL 3D Virtual Exhibition as a Media to Increase the Visibility of Digital Artwork - I Made Suandana Astika Pande; I Gede Bintang Arya Budaya; Padma Nyoman Crisnapati (Sekawan Institut, 2023)
The ongoing digital transformation continues to shape various domains, including the realm of art, which adopts social media to digitally promote artworks. Nonetheless, physical art exhibitions maintain their allure as they provide a direct experiential interaction for visitors. Consequently, the development of exhibition platforms that amalgamate user experience with accessibility becomes imperative. One emerging solution involves leveraging information technology and multimedia for virtualization, such as utilizing WebGL for creating a 3D Virtual Exhibition (3DVE). Employing the ADDIE methodology and evaluating it through the Technology Acceptance Model (TAM), the assessments affirm the robust performance and positive responses of 30 participants towards WebGL 3DVE. This development yields practical benefits, particularly for artists seeking to enhance the visibility of their creations. Furthermore, the inherent ease of use and broad accessibility can expand the potential audience for enjoying artworks. The percentage acceptance rates according to TAM validate favorable responses across usability (88%), ease of use (74%), satisfaction (90.6%), and technological acceptance (84.6%). Thus, the deployment of WebGL 3DVE in art exhibition development showcases strong potential in delivering a deeper and more inclusive experiential journey.